One-pot synthesis of ultrasmall MoO3 nanoparticles supported on SiO2, TiO2, and ZrO2 nanospheres: an efficient epoxidation catalyst - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Biradar, Ankush V. (Journal of Materials Chemistry A, 2014)
Ultrasmall molybdenum oxide (MoO3) nanoparticles supported on various (SiO2, TiO2 or ZrO2) nanospheres were synthesized in one pot using a reverse micelle method. The prepared catalysts were thoroughly characterized by various physico-chemical methods. TEM images showed uniform dispersion of MoO3 nanoparticles (1.5-4 nm) onto silica (similar to 275 nm). No separate MoO3 particles were identified from TEM for MoO3/TiO2 (similar to 10.5 nm) and MoO3/ZrO2 (similar to 6.5 nm) because AHM reacted with titanium and zirconium hydroxides to form solid solution. Among the prepared catalysts MoO3/SiO2 showed excellent catalytic activity (up to 90% conversion and 100% epoxide selectivity) for olefin epoxidation. The catalyst was successfully recycled up to five cycles without losing much activity and selectivity.

Bio-physical evaluation and in vivo delivery of plant proteinase inhibitor immobilized on silica nanospheres - Khandelwal, Neha; Doke, Dhananjay S.; Khandare, Jayant J.; Jawale, Priyanka V.; Biradar, Ankush V.; Giri, Ashok P. (Colloids and Surfaces B-Biointerfaces, 2015)
Recombinant expression of Capsicum annuum proteinase inhibitors (CanPI-13) and its application via synthetic carrier for the crop protection is the prime objective of our study. Herein, we explored proteinase inhibitor peptide immobilization on silica based nanospheres and rods followed by its pH mediated release in vitro and in vivo. Initial studies suggested silica nanospheres to be a suitable candidate for peptide immobilization. Furthermore, the interactions were characterized biophysically to ascertain their conformational stability and biological activity. Interestingly, bioactive peptide loading at acidic pH on nanospheres was found to be 62% and showed 56% of peptide release at pH 10, simulating gut milieu of the target pest Helicoverpa armigera. Additionally, in vivo study demonstrated significant reduction in insect body mass (158 mg) as compared to the control insects (265 mg) on 8th day after feeding with CanPI-13 based silica nanospheres. The study confirms that peptide immobilized silica nanosphere is capable of affecting overall growth and development of the feeding insects, which is known to hamper fecundity and fertility of the insects. Our study illustrates the utility and development of peptide-nanocarrier based platform in delivering diverse biologically active complexes specific to gut pH of H. armigera. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biodelivery; Helicovera armigera; Protein `corona'; Proteinase inhibitor; Silica nanospheres

Silica microspheres containing high density surface hydroxyl groups as efficient epoxidation catalysts - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Vanka, Kumar; Biradar, Ankush V. (RSC Advances, 2015)
Uniformly sized silica microspheres were synthesized by a hydrolysis-condensation method. The obtained material was etched with a mild aqueous potassium hydroxide solution for different periods of time to break their Si-O-Si bonds and increases the density of hydroxyl groups on their surfaces. The resulting materials were then used as transition metal-free catalysts for oxidation of olefins in the presence of hydrogen peroxide as a green oxidant. The materials were thoroughly characterized using various physicochemical techniques. These highly populated hydroxyl groups on the surface of silica microspheres were proven to be responsible for excellent conversion (up to 93%) and epoxide selectivity (up to 100%) for various olefins. Quantum mechanical calculations also corroborate the experimental findings. Furthermore, both experimental and theoretical studies show that tertiary silanols were present at the active sites of the catalyst surface and were responsible for olefin epoxidation.

Trifunctional mesoporous silica-based, highly active catalyst for one-pot, three-step cascade reactions - Biradar, Ankush V.; Patil, Vijayshinha S.; Chandra, Prakash; Doke, Dhananjay S.; Asefa, Tewodros (Chemical Communications, 2015)
We report the synthesis of a trifunctional catalyst containing amine, sulphonic acid and Pd nanoparticle catalytic groups anchored on the pore walls of SBA-15. The catalyst efficiently catalyzes one-pot three-step cascade reactions comprising deacetylation, Henry reaction and hydrogenation, giving up to similar to 100% conversion and 92% selectivity to the final product.

Efficient oxidation of ethyl benzene using in situ generated molybdenum acetylide oxo-peroxo complex as recyclable catalyst - Khomane, Sonali B.; Doke, Dhananjay S.; Dongare, M. K.; Halligudi, S. B.; Umbarkar, S. B. (Applied Catalysis A-General, 2017)
Selective oxidation of various alkanes/alkyl aromatics to corresponding carbonyl compounds has been carried out with very high conversion (similar to 98%) and selectivity (up to 100%) for carbonyl compounds using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and tert-butyl hydrogen peroxide (TBHP) as an oxidant and turnover number (TON) of 88 was obtained with turnover frequency (TOF) of 2.45 h(-1). Mo acetylide oxo-peroxo species is formed in situ by reaction of 1 with TBHP during the course of reaction as catalytically active species. Interestingly even though the catalytically active species is homogeneous in nature it could be recycled very easily by recovering the catalytically active species as solid after addition of diethyl ether, and separating the products into organic phase. In the case of ethyl benzene oxidation, even after three recycles no appreciable loss in ethyl benzene conversion and acetophenone selectivity was observed. This complex showed high catalytic activity for the oxo functionalization of other alkyl aromatics and alkanes such as substituted ethyl benzenes, toluene as well as cyclohexane. TBHP was found to be more efficient oxidant than hydrogen peroxide for this oxidation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Alkyl aromatics; Carbonyl compounds; Homogeneous catalysis; Molybdenum acetylide complex; Oxo-peroxo species

Environmentally benign bioderived carbon microspheres-supported molybdena nanoparticles as catalyst for the epoxidation reaction - Doke, Dhananjay S.; Umbarkar, Shubhangi B.; Gawande, Manoj B.; Zbori, Radek; Biradar, Ankush V. (ACS Sustainable Chemistry & Engineering, 2017)
A one pot synthesis of molybdenum oxide nanoparticles (NPs supported on bioderived carbon microspheres is reported. The catalyst was synthesized by the low temperature hydrothermal (LTH) method using D-glucose and bagasse as the carbon source. The carbonization of bagasse resulted in the formation of nonuniform carbon microspheres while glucose resulted in uniform carbon spheres. SEM and STEM elemental mapping show the uniform distribution of molybdenum oxide NPs over the carbon microspheres. XPS spectroscopy confirmed that molybdenum was in the Mo6+ oxidation state. The 1% MoO3 supported on carbon microspheres derived from D-glucose showed excellent catalytic activity up to 100% olefin conversion with 100% epoxide selectivity using organic tent-butyl hydroperoxide as an oxidant. The catalyst was successfully used for up to five cycles without losing substantial activity and selectivity.
Keywords: Carbon microspheres; epoxidation; heterogeneous catalysis; Hydrothermal synthesis; TBHP